2016
DOI: 10.1002/uog.15818
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal serum alpha‐fetoprotein at 12, 22 and 32 weeks' gestation in screening for pre‐eclampsia

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 19 publications
5
16
1
1
Order By: Relevance
“…The results were in general agreement with other studies on second-trimester MS-AFP and APOs [6,[9][10][11][12]. A case-control study on MS-AFP and preeclampsia also revealed that MS-AFP was elevated in both the first and the second trimesters in pregnancies that developed preeclampsia, but the performance of second-trimester MS-AFP combined with maternal factors for preeclampsia screening was better than that of first-trimester MS-AFP [23]. Taking others' and our findings together, we can conclude that first-trimester MS-AFP is less predictive of APOs than second-trimester MS-AFP.…”
Section: Discussionsupporting
confidence: 90%
“…The results were in general agreement with other studies on second-trimester MS-AFP and APOs [6,[9][10][11][12]. A case-control study on MS-AFP and preeclampsia also revealed that MS-AFP was elevated in both the first and the second trimesters in pregnancies that developed preeclampsia, but the performance of second-trimester MS-AFP combined with maternal factors for preeclampsia screening was better than that of first-trimester MS-AFP [23]. Taking others' and our findings together, we can conclude that first-trimester MS-AFP is less predictive of APOs than second-trimester MS-AFP.…”
Section: Discussionsupporting
confidence: 90%
“…For all these predictors, the performance was better for early than for late PE, and was better when assessed later in pregnancy than at 11–13 weeks, i.e. closer to the development of PE.…”
Section: Combined Screening Strategiesmentioning
confidence: 96%
“…Combined screening has been the subject of approximately 400 PubMed articles up to April 2018. Multiple studies have shown that women who go on to develop PE have, on average, higher mean arterial pressure, higher concentrations of maternal serum soluble fms‐like tyrosine kinase‐1 (sFlt‐1) and alpha‐fetoprotein (AFP), and lower concentrations of pregnancy‐associated plasma protein‐A (PAPP‐A) and PlGF, along with higher resistance in the uterine arteries, compared with women who do not. For all these predictors, the performance was better for early than for late PE, and was better when assessed later in pregnancy than at 11–13 weeks, i.e.…”
Section: Combined Screening Strategiesmentioning
confidence: 99%
“…Owing to the unknown cause, it is also described as 'unexplained elevated MS-AFP' in the literature. [4][5][6][7][8] However, the mechanism linking elevated MS-AFP and APO is obscure.…”
Section: Introductionmentioning
confidence: 99%